2008
DOI: 10.1016/j.jhydrol.2008.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of reforestation approaches on runoff control in the hilly red soil region of Southern China

Abstract: Summary Vegetation structure and soil properties are not only correlated with forest management practices, but also affect soil and water loss significantly. To estimate the long-term influences of regenerating forest cover on soil and water loss from degraded land, the runoff and soil loss in the context of different forest restoration approaches, including a control plot (CL) and plantations of slash pine (Pinus elliottii), Chinese fir (Cunninghamia lanceolata), tea-oil camellia (Camellia oleifera), and natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(63 citation statements)
references
References 22 publications
(31 reference statements)
4
45
1
8
Order By: Relevance
“…The bulk densities recorded for the top horizon in soils TS, MS and LS are similar to those recorded for many topsoils of red soils under different soil managements in southern China (e.g. Zheng et al, 2008;Huang et al, 2010) but the clay content was often less than 30 % in the soils studied.…”
Section: Structure and Porositysupporting
confidence: 73%
See 1 more Smart Citation
“…The bulk densities recorded for the top horizon in soils TS, MS and LS are similar to those recorded for many topsoils of red soils under different soil managements in southern China (e.g. Zheng et al, 2008;Huang et al, 2010) but the clay content was often less than 30 % in the soils studied.…”
Section: Structure and Porositysupporting
confidence: 73%
“…They cover 102 million ha, including ten provinces (Cao and Zhu, 1999;He et al, 2004;Wilson et al, 2004a;Zheng et al, 2008). They develop mainly in alluvial Quaternary sediments which reorganize materials resulting from continental alteration or in continental sediments from the Cretaceous or Eocene (BGMRHN, 1988;Wilson et al, 2004a and b;Hu et al, 2010;Shi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Wei et al (2007) indicated that soil water was at a better state at the early stage of tree plantation but not in the late stage. Some studies also showed that soil desiccation was developed under a 28-year-old tree plantation, and however better soil moisture was often observed under the natural forest or grassland (Zheng et al, 2008). In our study, all ecosystems had a poor soil water condition during the growing seasons.…”
Section: Effect Of Land Cover On Soil Water Variationmentioning
confidence: 45%
“…Wei et al (2007) reported that soil water content was higher in the early stage of a tree plantation than in the late stage. It has also been shown that soil desiccation developed under a 28-year-old tree plantation (Zheng et al 2008). The transition zones between an old and young plantation usually have significantly higher moisture content.…”
Section: Discussionmentioning
confidence: 99%